Understanding longitudinal muscle injury trends in youth football: Insights from U9 to U13 players - Skomrlj, J.; Modric, T.; Sekulic, D.; Kuko, M.; Cikojevic, L.; Bandalovic, A.; Turic, A.; Becir, B.; Veršic, Š. (Sports, 2025)
This longitudinal study investigated the incidence and characteristics of injuries among U9, U11, and U13 male football players in an academy setting over a six-season period, from 2016/17 to 2021/22. A total of 374 injuries were analyzed, with a particular focus on muscle injuries, including Delayed Onset Muscle Soreness (DOMS), muscle ruptures, and contusions. The study revealed that the highest injury incidence occurred in the U13 group, with quadriceps injuries being most prevalent in both the U13 and U11 groups. The study found that muscle injuries accounted for a significant proportion of all injuries, particularly in the U13 group, where muscle injuries increased over time. Intrinsic factors such as physical development during puberty and extrinsic factors like training intensity and psychological pressures may contribute to the higher injury rates in older age groups. Additionally, seasonal fluctuations in injury rates were observed, with a notable decline during the COVID-19 lockdowns in 2019/20 and 2020/21, followed by an increase post-lockdown due to deconditioning. The study highlights the vulnerability of young athletes to muscle injuries, particularly during growth spurts, and calls for further research into training methods and injury prevention strategies to mitigate these risks.